Comparisons of growth performance of African catfish (Clarias gariepinus BURCHELL, 1822) fingerlings fed different inclusion levels of black soldier fly (Hermetia illucens) larvae meal diets - Talamuk, Raphael (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.